PENINGKATAN KESEHATAN LANSIA MELALUI POSYANDU LANSIA DENGAN PENGAKTIFAN KEGIATAN SENAM LANSIA DI DESA PAGERNGUMBUK KECAMATAN WONOAYU KABUPATEN SIDOARJO: Array - Zulfa Rufaida; Sri Wardini Puji Lestari; Abdul Muhith (LPPM STIKes Buleleng, 2020)
The number of elderly people is increasing, therefore the government has formulated various health care policies aimed at improving the health status and quality of life of the elderly to achieve a happy and efficient old age in family and community life according to their existence. The purpose of this community service is to increase knowledge about the Elderly Posyandu and to be active in participating in elderly gymnastics. The methods used are lectures, discussions, role play and mentoring. The targets are the elderly in Pagerngumbuk Village, Wonoayu District, Sidoarjo Regency, the implementation of activities from April to June 2018. Data analysis uses frequency distribution. The results obtained, there were 34 participants with the mean pre-test and post-test scores of 87.94. The result is a significant increase in knowledge of 0.000 with a value of t = -16.85, and a 95% CI between -46.81 - -36.72, meaning that the effect is strong because it does not pass 1; giving treatment can increase 3-4x knowledge compared to not given. Meanwhile, for elderly exercise assistance, the number of participants averaged 27 people. The Posyandu Elderly counseling participants were enthusiastic about the material presented. There is an increase in the knowledge of the elderly about the role of the elderly Posyandu and the importance of elderly exercise. Health workers always provide information about the activities of the Elderly Posyandu to cadres, village officials and the community on an ongoing basis.